CRANIOFACIAL ASPECTS IN TURNER SINDROME - Dana Maria Albulescu; Preda Smaranda Adelina; Alexandru Dragos Ovidiu; Mihaela Jana Tuculina; Ruxandra Voinea-Georgescu; Bugala Narcis Mihaita (Romanian Society of Oral Rehabilitation, 2023)
Our study shows craniofacial morphological abnormalities in Turner syndrome by analyzing linear and angular variables calculated on cephalometry. Craniofacial aberrant aspects are found in reduction of the posterior base of the skull, mandibular and maxillary shortening, mandibular and maxillary retrusion. The values obtained by us are within the specific profile of this pathology, also reported to the specialized studies in the field, even if we were limited by the small number of cases, but we can affirm the importance of cephalometry in highlighting the craniofacial morphological features in Turner syndrome.